Hydrogen sulfide attenuates gastric mucosal injury induced by restraint water-immersion stress via activation of K(ATP) channel and NF-κB dependent pathway - Sun, Hong-Zhao (World J Gastroenterol, 2017)
AIM: To explore the effect of hydrogen sulfide (H(2)S) on restraint water-immersion stress (RWIS)-induced gastric lesions in rats and the influence of adenosine triphosphate (ATP)-sensitive potassium (K(ATP)) channels and nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) pathway on such an effect. METHODS: Male Wistar rats were randomly divided into a control group, a physiological saline (PS) group, a sodium hydrosulfide (NaHS) group, a glibenclamide (Gl) group, Gl plus NaHS group, a pyrrolidine dithiocarbamate (PDTC) group, and a PDTC plus NaHS group. Gastric mucosal injury was induced by RWIS for 3 h in rats, and gastric mucosal damage was analyzed after that. The PS, NaHS (100 μmol/kg body weight), Gl (100 μmol/kg body weight), Gl (100 μmol/kg or 150 μmol/kg body weight) plus NaHS (100 μmol/kg body weight), PDTC (100 μmol/kg body weight), and PDTC (100 μmol/kg body weight) plus NaHS (100 μmol/kg body weight) were respectively injected intravenously before RWIS. RESULTS: RWIS induced serious gastric lesions in the rats in the PS pretreatment group. The pretreatment of NaHS (a H(2)S donor) significantly reduced the damage induced by RWIS. The gastric protective effect of the NaHS during RWIS was attenuated by PDTC, an NF-κB inhibitor, and also by glibenclamide, an ATP-sensitive potassium channel blocker, in a dose-dependent manner. CONCLUSION: These results suggest that exogenous H(2)S plays a protective role against RWIS injury in rats, possibly through modulation of K(ATP) channel opening and the NF-κB dependent pathway.